Get detailed and accurate answers to your questions on IDNLearn.com. Discover prompt and accurate answers from our community of experienced professionals.

Use the given conditions to write an equation for the line in point-slope form. The line passes through [tex]\((8,2)\)[/tex] and [tex]\((4,8)\)[/tex].

A. [tex]\( y - 2 = -\frac{3}{2}(x - 8) \)[/tex] or [tex]\( y - 8 = -\frac{3}{2}(x - 4) \)[/tex]

B. [tex]\( y + 2 = -\frac{3}{2}(x + 8) \)[/tex] or [tex]\( y + 8 = -\frac{3}{2}(x + 4) \)[/tex]

C. [tex]\( y - 2 = -\frac{3}{2}(x - 4) \)[/tex] or [tex]\( y - 8 = -\frac{3}{2}(x - 8) \)[/tex]

D. [tex]\( y - 2 = 8(x + 8) \)[/tex] or [tex]\( y - 8 = 4(x - 2) \)[/tex]


Sagot :

To find the equation of the line in point-slope form that passes through the points [tex]\((8,2)\)[/tex] and [tex]\((4,8)\)[/tex], follow these steps:

1. Determine the slope (m):
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Here, the coordinates of the first point [tex]\((x_1, y_1)\)[/tex] are [tex]\((8,2)\)[/tex], and the coordinates of the second point [tex]\((x_2, y_2)\)[/tex] are [tex]\((4,8)\)[/tex].

Substituting the values:
[tex]\[ m = \frac{8 - 2}{4 - 8} = \frac{6}{-4} = -\frac{3}{2} \][/tex]

2. Using the slope (m) and point-slope form:
The point-slope form of the equation of a line is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
We can use either of the points [tex]\((8, 2)\)[/tex] or [tex]\((4, 8)\)[/tex] to write our equation.

- Using the point [tex]\((8, 2)\)[/tex]:
[tex]\[ y - 2 = -\frac{3}{2}(x - 8) \][/tex]

- Using the point [tex]\((4, 8)\)[/tex]:
[tex]\[ y - 8 = -\frac{3}{2}(x - 4) \][/tex]

Therefore, the equations for the line in point-slope form using the given points are:
[tex]\[ y - 2 = -\frac{3}{2}(x - 8) \quad \text{or} \quad y - 8 = -\frac{3}{2}(x - 4) \][/tex]

Given the options:

A. [tex]\(y - 2 = -\frac{3}{2}(x - 8)\)[/tex] or [tex]\(y - 8 = -\frac{3}{2}(x - 4)\)[/tex]

B. [tex]\(y + 2 = -\frac{3}{2}(x + 8)\)[/tex] or [tex]\(y + 8 = -\frac{3}{2}(x + 4)\)[/tex]

C. [tex]\(y - 2 = -\frac{3}{2}(x - 4)\)[/tex] or [tex]\(y - 8 = -\frac{3}{2}(x - 8)\)[/tex]

D. [tex]\(y - 2 = 8(x + 8)\)[/tex] or [tex]\(y - 8 = 4(x - 2)\)[/tex]

Option A is the correct one:
[tex]\[ y - 2 = -\frac{3}{2}(x - 8) \quad \text{or} \quad y - 8 = -\frac{3}{2}(x - 4) \][/tex]